5-(2a-3)=7-(3a+5)

Simple and best practice solution for 5-(2a-3)=7-(3a+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-(2a-3)=7-(3a+5) equation:


Simplifying
5 + -1(2a + -3) = 7 + -1(3a + 5)

Reorder the terms:
5 + -1(-3 + 2a) = 7 + -1(3a + 5)
5 + (-3 * -1 + 2a * -1) = 7 + -1(3a + 5)
5 + (3 + -2a) = 7 + -1(3a + 5)

Combine like terms: 5 + 3 = 8
8 + -2a = 7 + -1(3a + 5)

Reorder the terms:
8 + -2a = 7 + -1(5 + 3a)
8 + -2a = 7 + (5 * -1 + 3a * -1)
8 + -2a = 7 + (-5 + -3a)

Combine like terms: 7 + -5 = 2
8 + -2a = 2 + -3a

Solving
8 + -2a = 2 + -3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
8 + -2a + 3a = 2 + -3a + 3a

Combine like terms: -2a + 3a = 1a
8 + 1a = 2 + -3a + 3a

Combine like terms: -3a + 3a = 0
8 + 1a = 2 + 0
8 + 1a = 2

Add '-8' to each side of the equation.
8 + -8 + 1a = 2 + -8

Combine like terms: 8 + -8 = 0
0 + 1a = 2 + -8
1a = 2 + -8

Combine like terms: 2 + -8 = -6
1a = -6

Divide each side by '1'.
a = -6

Simplifying
a = -6

See similar equations:

| I-17.4=35 | | 2m^2-22m-52=0 | | 3u-3u+4u-3+1=19 | | 3i/6-2i | | 2y+4x=2y-2x | | X+(X*0.0495)=28 | | 6x-2(2-x)=4(2r-1) | | 7a-6a+2a+1=19 | | g(x)=/x1 | | 2x-17=7x+3 | | 4x-3x+4=16 | | -24=12d | | 3t-2t-1=15 | | 2x+7x-8=19 | | 15p-12p-p+3=17 | | 15-12p-p+3=17 | | I-17.4=33 | | 11h-11h+h=20 | | 2(t+5)=7 | | 2r-r+4r-3r=20 | | 16=-16t^2+24t+0 | | D-1890=8242 | | -8x(x+1)-8=6-9x | | 15y-11y+6y=10 | | 6g-4g+g-3g+g=17 | | 11/3×12/1= | | 15h-11h=12 | | x+12=9x-5 | | 14m-13m=5 | | 7a+a=16 | | x(1/3)(3) | | 4(7x+y)= |

Equations solver categories